ANALISIS PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN PERKOSAAN INSES YANG MELAKUKAN ABORSI PADA TINGKAT PEMERIKSAAN PENGADILAN (STUDI KASUS PUTUSAN NOMOR 5/PID.SUS.ANAK/2018/PN.MBN.) - Febefitriany Kusnadi; Hery Firmansyah (Jurnal Hukum Adigama, 2019)
Law Number 36 Year 2009 regarding Health still gives room for abortion for a certain reason, namely by reason of medical indications, but medical indications in the law only state the limits, where incest rapes can be used as medical indications for having an abortion so that the crime is abolished. The problem faced is whether there is a violation of procedural law at the examination at the Muara Bulian District Court, related to decision  of  number .5/Pid.Sus.Anak/2018/PN.Mbn and how the legal protection of women victims of incest rape who have an abortion at the court examination level (Study of Case of Decision Number 5/Pid.Sus.Anak/2018/PN.Mbn). Method of research used in writing this thesis is normative legal research. The results showed that violations of the WA during the examination period at Muara Bulian District Court, Jambi were the detention of children who were raped, where the Defendant was still a child category and during the trial process was detained, the child victims of rape clearly needed protection from the trauma of rape experienced. the need for psychosocial assistance from the time of treatment to recovery; and the provision of protection and assistance at every level of the examination starting from the investigation, prosecution, until the examination in the court hearing.